Linking Arctic stratospheric polar vortex weakening to rising CO2-induced intensification of the Indo-Pacific warm pool during the past five decades - Lejiang Yu; Shiyuan Zhong; Cuijuan Sui; Bo Sun (Environmental Research Letters, 2023)
Accompanying the global rise in greenhouse gas emissions, a warming trend in the Indo-Pacific warm pool (IPWP) has exerted a discernible influence on tropical atmosphere–ocean interactions. However, the impact of this intensification of the IPWP on the Arctic stratospheric polar vortex (ASPV) remains unclear. In this study, we revealed a link between the changes in the IPWP and ASPV during the early winter months, with nearly half of the weakening in the ASPV attributable to the intensification of the IPWP from 1968 to 2020. Wave trains triggered by the elevated SST in the IPWP region lead to enhanced eastward-propagating flux convergence in the northern high-latitude stratosphere, ultimately resulting in a diminishing ASPV. With increasing atmospheric greenhouse gas, the ASPV is poised to further weaken in the future, particularly in the context of a more intense IPWP. Our finding has significant implications for early winter ASPV strength and location prediction and seasonal weather forecasting.